If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(k + 11) = -288 Reorder the terms: -9(11 + k) = -288 (11 * -9 + k * -9) = -288 (-99 + -9k) = -288 Solving -99 + -9k = -288 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '99' to each side of the equation. -99 + 99 + -9k = -288 + 99 Combine like terms: -99 + 99 = 0 0 + -9k = -288 + 99 -9k = -288 + 99 Combine like terms: -288 + 99 = -189 -9k = -189 Divide each side by '-9'. k = 21 Simplifying k = 21
| 7x+18=85 | | -12-7a=-5(a+4) | | 45=x+62+x+87 | | 9x+13=59 | | 38x+31=563 | | -30-6x=-6(3x-7) | | 17x+6=106 | | 16-3m=7-6(m+2) | | 10x-25=105 | | 80+x=171 | | 34+4x=-5(x+4) | | -3x-3(1+1)=-15 | | 55x=605 | | 2x+-2=10-4 | | 4y+9=17-2y | | 43+x=410 | | x-24=64 | | -3X^2+90=0 | | 5x=430 | | 4x-5y-9x+8y=0 | | 2x^2-lnx+1=0 | | 90-x^2=0 | | -x+3+12x=-4+4x+42 | | 5x-15x^3=5x(1-3x^2) | | (x+8)+4=x+(4+8) | | 3w^2-10w+8=0 | | -4(2+3n)=-56 | | 2(a+3)=5a-1 | | -4-4(2+4v)=-44 | | a-4(2a+4)=-44 | | 10a=45 | | 3(2+4x)=-42 |